Redefining tax progressivity in developing countries: The Progressive Vertical Index - Ricardo Guerrero Fernandez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Recent evidence from developing countries shows that the bottom of the income distribution pays more taxes relative to their income than the top 1%, highlighting a lack of tax progressivity in these societies. Current measures of tax progressivity fail to indicate which part of the income distribution explains this. Following the Palma Ratio intuition, this paper introduces the concept of vertical progressivity and a new index, the Progressive Vertical Index (PVI), which assesses the relationship between the tax burdens of the top 1% and the bottom 50% of the population. Using a novel dataset on tax rates in 10 Latin American countries from 2000 to 2020, the paper tests the PVI by comparing the results with the Kakwani index. The PVI is shown to offer an intuitive and transparent instrument for measuring the comparative tax burdens of the richest and poorest groups, thereby indicating that the problem of achieving tax progressivity in developing countries lies in correctly assessing the relationship between the effective tax rates paid by the rich and poor.
Keywords: C23; D31; H22; 330; income distribution; tax progressivity; effective tax rates; income inequality; Latin America